Spirituality and Social Media: Connecting the Dots - Rautela, Sonica; Sharma, Adya (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Spirituality has gained the interest of all generations in the past few years. The concept of spirituality is very old but its popularity in the last few decades is worth noticing. Today spirituality is making inroads in different sectors like health sector, education, working culture etc. Social media on the other hand is a relatively new phenomenon which has changed the world forever. The impact and reach of social media is the maximum among all media tools. With the increased use of smart phone and other interactive technologies social media usage has grown with huge leaps and bounds.  The paper tries to find a link to connect the old with new in search of a principled life as advocated by spirituality. The paper explores the journey of Spirituality and its usefulness in current context. The paper then traces the rise and impact of social media. The paper concludes by proposing a conceptual model that depicts use of social media to educate about spirituality. The integrative approach identifies the positive aspects of social media to reach out to people.